Predicted standard deviation of proficiency testing performance in animal nutrition methods. - SOUZA, G. B. de (2021)
The empirical correlations of the results of over ten years of a proficiency testing of animal nutritional analysis conducted by Embrapa were evaluated. The results demonstrate the similarity of the Horwitz equation proposal, but it is desirable to use individual equations related to the different analyses performed by the laboratories. Using these equations enables a more realistic assessment of possible systematic errors and analytical processes, improving laboratory performance and providing the most reliable results.